2007
DOI: 10.1111/j.1471-4159.2007.04841.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of pro‐survival Akt and ERK1/2 signalling pathways underlie the anti‐apoptotic effects of flavanones in cortical neurons

Abstract: There is growing interest in the potential beneficial effects of flavonoids in the aging and diseased brain. We have investigated the potential of the flavanone hesperetin and two of its metabolites, hesperetin-7-O-b-D-glucuronide and 5-nitro-hesperetin, to inhibit oxidative stress-induced neuronal apoptosis. Exposure of cortical neurons to hydrogen peroxide led to the activation of apoptosis signal-regulating kinase 1 via its de-phosphorylation at Ser963, the phosphorylation of c-jun N-terminal kinase and c-J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
199
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 236 publications
(209 citation statements)
references
References 68 publications
(166 reference statements)
10
199
0
Order By: Relevance
“…One example of this is the flavonol quercetin and some of its in vivo metabolites which were shown to inhibit prosurvival Akt/PKB signaling pathways by inhibiting PI3-kinase activity, 83 whereas flavanones, such as hesperetin, have been shown to activate Akt/PKB signaling to confer prosurvival properties in cortical neurons. 108 Furthermore, it has been shown that EGCG stimulates extracellular signal-regulated kinase (ERK)-and PI3K-dependent increase in CREB phosphorylation and upregulates GluR2 levels in cortical neurons and can therefore act as a modulator in neurotransmission, plasticity, and synaptogenesis. 107 Supplementing the diet of aged animals with blueberry for 12 weeks, has been shown to induce the phosphorylation of hippocampal Akt, the activation downstream of mTOR, and the increased expression of activity-regulated cytoskeletal-associated protein (Arc/Arg3.1).…”
Section: ■ Flavonoids and Their Interaction With Signaling Pathwaysmentioning
confidence: 99%
“…One example of this is the flavonol quercetin and some of its in vivo metabolites which were shown to inhibit prosurvival Akt/PKB signaling pathways by inhibiting PI3-kinase activity, 83 whereas flavanones, such as hesperetin, have been shown to activate Akt/PKB signaling to confer prosurvival properties in cortical neurons. 108 Furthermore, it has been shown that EGCG stimulates extracellular signal-regulated kinase (ERK)-and PI3K-dependent increase in CREB phosphorylation and upregulates GluR2 levels in cortical neurons and can therefore act as a modulator in neurotransmission, plasticity, and synaptogenesis. 107 Supplementing the diet of aged animals with blueberry for 12 weeks, has been shown to induce the phosphorylation of hippocampal Akt, the activation downstream of mTOR, and the increased expression of activity-regulated cytoskeletal-associated protein (Arc/Arg3.1).…”
Section: ■ Flavonoids and Their Interaction With Signaling Pathwaysmentioning
confidence: 99%
“…Flavonoids may improve cognitive performance by protecting vulnerable neurons, enhancing existing neuronal function, and stimulating neuronal regeneration (10). Flavonoids exert effects on long-term potentiation underlying learning and memory, on and consequently memory and cognitive performance, through their interactions with the signaling pathways including PI3K/Akt (11) and MAPK (12).…”
mentioning
confidence: 99%
“…Instead, recent findings have suggested that in lower amounts, typical of those attained in the diet, polyphenols may exert pharmacological activity within the cells with mechanisms that go beyond the classic antioxidant scavenging mechanisms (Williams et al, 2004;Vauzour et al, 2010). In particular, polyphenols are capable of modulating intracellular signalling cascades Vauzour et al, 2010;Kuo et al, 2015), gene expression and interactions with mitochondria (Schroeter et al, 2001;Schroeter et al, 2007;Vauzour et al, 2007b;Mandel et al, 2008). By affecting such pathways, they have the potential to induce new protein synthesis in neurons and thus an ability to induce morphological changes, which have a direct influence on memory acquisition, consolidation and storage.…”
Section: Effects Of Polyphenols On Age-related Cognitive Decline and mentioning
confidence: 99%
“…There is much evidence to support the actions of polyphenols on the ERK pathway (Schroeter et al, 2007;Vauzour et al, 2007b), which often leads to the activation of CREB (Corona et al, 2013), a transcription factor considered to be critical in the induction of long-lasting changes in synaptic plasticity and memory (Bourtchuladze et al, 1994;Impey et al, 1998). Indeed, CREB activation regulates the expression of a number of important genes, including the brain derived neurotrophic factor (BDNF), thus playing a pivotal role in controlling neuronal survival, and synaptic function in the adult central nervous system (Finkbeiner, 2000;Tully et al, 2003).…”
Section: Polyphenols Affect Signalling Cascades Involved In Synaptic mentioning
confidence: 99%